2022
DOI: 10.2174/1874467214666210126112839
|View full text |Cite
|
Sign up to set email alerts
|

Inactivation of Parathyroid Hormone: Perspectives of Drug Discovery to Combating Hyperparathyroidism

Abstract: : Hormonal coordination is tightly regulated within the human body and thus regulates human physiology. The parathyroid hormone (PTH), a member of the endocrine system, regulates the calcium and phosphate level within the human body. Under non-physiological conditions, PTH levels get upregulated (hyperparathyroidism) or downregulated (hypoparathyroidism) due to external or internal factors. In the case of hyperparathyroidism, elevated PTH stimulates cellular receptors present in the bones, kidneys, and intesti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 146 publications
0
2
0
Order By: Relevance
“…For proPTH the competition with PTH represents one perspective for drug development to treat hyperparathyroidism. As PTH 1–84 and PTH 1–34 and their formulations are already approved drugs for the treatment of osteoporosis [4] we anticipate that competing proPTH might serve as a compound for a proper blood level adjustment during hormone therapy. Functional amyloids of hormones had been put into perspective as a formulation of long‐acting drugs [42].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For proPTH the competition with PTH represents one perspective for drug development to treat hyperparathyroidism. As PTH 1–84 and PTH 1–34 and their formulations are already approved drugs for the treatment of osteoporosis [4] we anticipate that competing proPTH might serve as a compound for a proper blood level adjustment during hormone therapy. Functional amyloids of hormones had been put into perspective as a formulation of long‐acting drugs [42].…”
Section: Discussionmentioning
confidence: 99%
“…The induced cascade via heterotrimeric G proteins converts the signal into a modulated flow of second messengers including cyclic AMP (cAMP), inositol triphosphate, diacylglycerol, or cGMP [2]. As these second messengers modulate skeletal, endocrine, cardiovascular, or nervous cell function [3], PTH 1–84 and PTH 1–34 are approved drugs against osteoporosis [4]. In PTH‐secreting parathyroid tissue derived from both normal and overactive parathyroid glands, early studies identified intrafollicular amyloids [5].…”
Section: Figmentioning
confidence: 99%